Age‐, sex‐, and subregion‐specific properties of distal fibular microarchitecture and strength: An ex vivo HR‐pQCT study. Issue 2 (16th May 2022) - Schlickewei, Carsten; Schweizer, Conradin; Püschel, Klaus; Ondruschka, Benjamin; Kleinertz, Holger; Barg, Alexej; Rolvien, Tim; Stürznickel, Julian
Abstract: Despite its clinical relevance in the context of ankle fractures, little is known about the bone microarchitecture and strength of the distal fibula, especially regarding age‐, sex‐, and subregion‐specific effects. To address this gap of knowledge, we obtained fibulae from 30 skeletally intact donors at autopsy (each 15 male and female), which were analyzed by high‐resolution peripheral quantitative computed tomography including micro‐finite element analysis. Scans were performed in a 7‐cm volume of interest and evaluated in three subregions according to the Danis‐Weber fracture classification. Group comparisons and linear regression analyses were applied to evaluate the effects of age, sex, and subregion. From distal to proximal, we observed an increase of cortical parameters and a decrease of trabecular parameters. Age was primarily associated with a cortical decrease in all subregions (Danis‐Weber type A, B, and C) in women. While women showed a greater magnitude of decline, men also exhibited an age‐associated decrease for some parameters, including cortical area and cortical thickness in the type C subregion. Stiffness and failure load were highest in the type C subregion in both women and men. A critical age‐related decline in bone strength parameters in the type B subregion was observed in women, providing an explanation for the increased incidence of low‐traumatic type B fractures in the elderly. Together, these findings extend the current understanding of distal fibular microarchitecture, likely explaining the epidemiologic features of distal fibula fractures and emphasizing the need for age‐adapted treatment algorithms.